Nurses’ knowledge of and attitude toward postoperative patient-controlled analgesia (PCA) and the associated factors - Ying-Ru Chen; Cheryl Chia-Hui Chen; Wei-Wen Wu; Fu-Ing Tang; Ling-Chun Lu (BMC Nursing, 2024)
Abstract Background Postoperative pain control is pivotal for surgical care; it facilitates patient recovery. Although patient-controlled analgesia (PCA) has been available for decades, inadequate pain control remains. Nurses’ knowledge of and attitude toward PCA may influence the efficacy on clinic application. Purpose The purpose of this study is to evaluate nurses’ knowledge of and attitude toward postoperative PCA and investigate the associated factors. Methods This is a cross-sectional study. We enrolled registered nurses from a 2200-bed medical center in northern Taiwan within one year. The participants completed an anonymous self-reported PCA knowledge inventory and PCA attitude inventory. Data were analyzed descriptively and associated were tested using logistic regression. Results With 303 participants enrolled, we discovered that nurses had limited knowledge of and a negative attitude toward PCA. Under half of the participants know how to set up a bolus dose and lockout intervals. The majority held misconceptions regarding side effect management for opioids. The minority agree to increase the dose when a patient experienced persistent pain or suggested the use of PCA. Surprisingly, participants with a bachelor’s or master’s degree had lower knowledge scores than those with a junior college degree. Those with 6–10 years of work experience also are lower than those with under 5 years of experience. However, the participants with experience of using PCA for patient care had higher knowledge scores and a more positive attitude. Conclusions Although postoperative PCA has been available for decades and education programs are routinely provided, nurses had limited knowledge of and a negative attitude toward PCA. A higher education level and longer work experience were not associated with more knowledge. The current education programs on PCA should be revised to enhance their efficacy in delivering up-to-date knowledge and situation training which may convey supportive attitude toward clinical application of PCA.